The relationship between social and psychological factors with cognitive impairment after stroke: a prospective study - Li, Yao; Tang, Aijie; Ge, Lili; Zhang, Lin; Chen, Ling; Xu, Yuhua; Wang, Li; Zhu, Xiaoping; Wu, Qian (Frontiers in Psychiatry, 2024)
Objectives To investigate the association between social and psychological factors and the risk of cognitive impairment following acute ischemic stroke. Materials and methods A prospective study was conducted at Shanghai Tenth People’s Hospital from June 2021 to July 2022. The study focused on social and psychological factors, which were assessed using the Social Support Rating Scale (SSRS), Self-Perceived Burden Scale (SPBS), and Hamilton Depression Scale (HAMD) within 3 days after admission to the hospital. Cognitive function was evaluated using the Montreal Cognitive Assessment at 3 months post-stroke. Logistic hierarchical regression models were used to examine the association between these three indicators and cognitive impairment following a stroke. Results Among these patients, cognitive function was assessed in 211 cases at the 3-month follow-up after the initial stroke event. At 3 months post-stroke, 118(55.9%) of the participants experienced cognitive impairment, while 93(44.1%) did not. The scores on the SPBS and HAMD showed significant associations with cognitive impairment at 3 months after stroke. The scores of SPBS [scores: 30~39 vs.<20 points, odds ratio (OR)=2.993 (1.135–7.896); scores: ≥40 vs.<20points, OR=7.382 (1.117–48.799); P=0.043] and the HAMD [scores: >7 vs.≤7 points, OR=3.287(1.362~7.936); P=0.008]. There were no significant associations observed between SSRS and PSCI. Conclusion Early screening for depressive symptoms and focusing on self-perceived burden can be beneficial for decision support for clinicians and improve cognitive function recovery at the 3-month mark post-stroke.